PEMBAHARUAN HUKUM TENTANG PENARIKKAN JAMINAN FIDUSIA YANG TIDAK SESUAI DENGAN UU NO.42 TAHUN 1999 - Adinda Putri Elin; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Arrangements regarding fiduciary guarantees are contained in Law Number 42 of 1999. Fiduciary is a guarantee of trust in a relationship based on feelings between humans and other humans where they feel safe so they have the trust to give property as a place of debt. However, if circumstances state that the debtor has breached the contract, the creditor will execute or withdraw the fiduciary guarantee based on Article 15 of the Fiduciary Law, where the creditor has executorial power in unilaterally declaring a breach of contract against the debtor and then using the debt collector to withdraw the fiduciary guarantee. in withdrawing the guarantee, some debt collectors used violence. This is contrary to Article 28G paragraph (1) of the 1945 Constitution which explains that every person has the right to protection for itself, family, honor, dignity and property under ourselves control, and has the right to feel safe and protected from threats of fear to do or not doing something which is a human right The Constitutional Court issued a decision on review of laws and regulations, namely Law Number 42 of 1999 concerning Fiduciary Guarantees. First, in 2019, MK Decision No. 18/PUU-XVII/2019, then in 2021 No. 2/PUU-XIX/2021 in these two decisions there is no difference, only the same confirmation. The Constitutional Court's decision resulted in a statement of several phrases regarding Article 15 paragraph (2) and paragraph (3) of the Fiduciary Law, namely the first is the phrase “Parate Execution“ and